2013
DOI: 10.1038/bjc.2013.226
|View full text |Cite|
|
Sign up to set email alerts
|

Prevalence of the metabolic syndrome and cardiovascular disease risk in chemotherapy-treated testicular germ cell tumour survivors

Abstract: Background:Testicular cancer patients have an increased risk for cardiovascular disease (CVD), which might be related to the increased prevalence of the metabolic syndrome (MetS) in this group of patients.Methods:We assessed the prevalence of MetS and calculated the 10-year CVD risk in a cohort of 255 testicular germ cell tumour survivors (median age, 38.7 years; interquartile range, 31–48) at a mean of 7.8 years after anti-cancer treatment, and compared these with data obtained from 360 healthy men.Results:Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 36 publications
(47 reference statements)
6
61
0
1
Order By: Relevance
“…The prevalence of the metabolic syndrome is higher among patients treated with cisplatin-based chemotherapy than among controls or other treatment groups [55,56,58], with prevalence rates ranging between 17% and 34% several years after cisplatin-based chemotherapy [51,55,58].…”
Section: Cardiovascular Risk Factors and Endothelial Dysfunctionmentioning
confidence: 96%
See 2 more Smart Citations
“…The prevalence of the metabolic syndrome is higher among patients treated with cisplatin-based chemotherapy than among controls or other treatment groups [55,56,58], with prevalence rates ranging between 17% and 34% several years after cisplatin-based chemotherapy [51,55,58].…”
Section: Cardiovascular Risk Factors and Endothelial Dysfunctionmentioning
confidence: 96%
“…Furthermore, diabetes is more frequent after infradiaphragmatic RT when comparison with healthy controls and patients treated with surgery only [51,53], with a reported prevalence rate of 10% after 20 years of follow-up. Several studies have also reported an increased risk for hypercholesterolemia after cisplatin-based chemotherapy [10,35,55,56], with reported rates of 67% to 84%.…”
Section: Cardiovascular Risk Factors and Endothelial Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Nuver et al found the prevalence of MetS was approximately 4-fold increased among orchiectomized GCC patients compared with healthy controls [14], while a recent study found no difference in MetS prevalence between these GCC survivors and their healthy counterparts [15]. The diversity of these findings may be due to differences in diagnostic definitions of MetS and potential suboptimal dataset with national/regional differences in clinical follow-up proceedings.…”
Section: Germ Cell Cancer Managementmentioning
confidence: 99%
“…35 DIABETES AND METABOLIC SYNDROME 31 TESTICULAR CANCER Testicular cancer patients have an increased risk for CVD, which might be related to the increased prevalence of the metabolic syndrome in this group of patients. 36 A recent study assessed the prevalence of metabolic syndrome and the 10-year CVD risk in a cohort of 255 testicular germ cell tumour survivors (median age, 38.7 years; interquartile range, 31-48) at a mean of 7.8 years after anticancer treatment, and compared these with data obtained from 360 healthy men. The survivors had an age-adjusted increased risk for metabolic syndrome of 1.9 compared with that of healthy controls.…”
Section: Bladder Cancermentioning
confidence: 99%